Diamond Care Centre / Liyana Lily Mahmud ... [et al.] - Mahmud, Liyana Lily; Vincent, Sonja Anne; Anuar, Suriati; Dorani, Rasidah; Ramli, Siti Khamisah (2011)
This is the first proposal that we finished while we studying in University Technology Mara (UiTM). In our group, we have five members among us and each person have own task and responsibility which are General Manager, Administration Manager, Marketing Manager, Operation Manager and Financing Manager and all of members are women. We have established one daycare centre from we have choose this business that we had discussed among us and agreed. Daycare centre is a centre that care children for those parents cannot care his/her children because of several reasons for instance have own career or others reason. For our business, we had decided to name our business as Diamond Care Centre. the reason why we choose that name of business because our service is about care the children, then we combined it into diamond because the value of diamond is too valuable and we take the valuable as our principle to care children in a proper way, and assume them valuable like a diamond. A preparation is needed to establish this business, therefore we had made all position in term of administration, marketing, operation and budget from financial. Each position have own manager and each manager have own task. In Marketing, manager'sresponsibilityto market this business to customers. Other than that, to do sale forecast, find the competitor advantages and disadvantages. Operation position responsibilities to measure all the facilities or items are complete and manage operate the business. Administration position is admin the employee for instance manages the salary, bonus, EPF, SOCSO and so on. Financial site is to prepare the budget either the capital enough or not, make loan, do cash flow to see how business running, gains profit or deficit. In conclusion, all of the managers' position must cooperate together to achieve goals, aims and profit, without these cooperation, it is hard to make business plan.